Factors associated with the worsening of COVID-19 symptoms among cohorts in community- or home-isolation care in southern Thailand - Sila, Thanit; Suriyaamorn, Wisanuwee; Toh, Chanavee; Rajborirug, Songyos; Surasombatpattana, Smonrapat; Thongsuksai, Paramee; Kongkamol, Chanon; Chusri, Sarunyou; Sornsenee, Phoomjai; Wuthisuthimethawee, Prasit; Chaowanawong, Raya; Sangkhathat, Surasak; et al. (Frontiers in Public Health, 2024)
Introduction This study aimed to investigate factors associated with time-to-referral due to worsening symptoms in patients with laboratory-confirmed COVID-19 in southern Thailand. While underlying diseases have been evaluated to assess COVID-19 severity, the influence of vaccinations and treatments is also crucial. Methods A cohort of 8,638 patients quarantined in home or community isolation with laboratory-confirmed COVID-19 was analyzed. Survival analysis and the Cox proportional hazard ratio were employed to assess factors influencing time-toreferral. Results Age ≥ 60 years, neurologic disorders, cardiovascular disease, and human immunodeficiency virus infection were identified as significant risk factors for severe COVID-19 referral. Patients who received full- or booster-dose vaccinations had a lower risk of experiencing severe symptoms compared to unvaccinated patients. Notably, individuals vaccinated during the Omicron-dominant period had a substantially lower time-to-referral than those unvaccinated during the Delta-dominant period. Moreover, patients vaccinated between 1 and 6 months prior to infection had a significantly lower risk of time-to-referral than the reference group. Discussion These findings demonstrate early intervention in high-risk COVID-19 patients and the importance of vaccination efficacy to reduce symptom severity. The study provides valuable insights for guiding future epidemic management strategies and optimising patient care during infectious disease outbreaks.